PERANCANGAN APLIKASI KOMPRESI PADA APLIKASI PEMUTAR AUDIO DENGAN MENGGUNAKAN METODE GOHECOTWO COMPRESSION - Harefa, Misael Oktavianda; Hondro, Rivalri Kristianto; Yanny, Anda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Many people enjoy listening to music on their mobile devices, as cited from Kompas Tekno. Audio files can take up a lot of storage space, especially high-quality audio files. Another issue is that although there are many audio player applications available, only a few offer audio compression features, making it difficult for users to compress their audio files. The existing audio compression applications often do not utilize optimal compression methods, which can result in poor audio quality or low compression rates. Moreover, although many audio player applications are available, few provide audio compression features, making it hard for users to compress their files. Additionally, the current audio compression applications do not often use optimal compression methods, leading to poor audio quality or low compression efficiency. One solution to this problem is using an audio compression application that can reduce the size of audio files without significantly reducing the audio quality. This allows users to store more audio files on their mobile devices.